Geographic Variation in Social Vocalizations of the Great Himalayan Leaf-Nosed Bat, Hipposideros armiger: Acoustic Overflow Across Population Boundaries - Lin, Aiqing; Feng, Jiang; Kanwal, Jagmeet S. (Frontiers in Ecology and Evolution, 2022)
Bat populations employ rich vocal repertoires for social communication besides emitting sound pulses for echolocation. Acoustic parameters of echolocation pulses can vary with the context in which they are emitted, and also with the individual and across populations as a whole. The acoustic parameters of social vocalizations, or “calls”, also vary with the individual and context, but not much is known about their variation across populations at different geographic locations. We hypothesized first, that individuals within geographically dispersed populations communicate using spectrographically similar constructs or syllable types that vary discordantly with the correlation pattern for echolocation pulses across those same geographic regions. Second, that the variance in a syllable type is acoustically universal across subspecies populations, i.e., the acoustic boundaries of a syllable type are not uniquely constrained to its variation within a particular population. We leveraged the detailed acoustic classification of social vocalizations available for the Great Himalayan leaf-nosed bat, Hipposideros armiger armiger, to examine geographic variation in five commonly emitted simple syllable types. To test our hypotheses, we obtained recordings of social calls of this species from nine locations within the geopolitical borders of China. These were consolidated into five geographic regions based on previously established region-specific differences in the peak frequency of echolocation pulses. A multivariate cluster analysis established that unlike echolocation pulses, syllable types exhibit a relatively large variance. Analysis of this variance showed significant differences in Least Squares Means estimates, establishing significant population-level differences in the multiparametric means of individual syllable types across geographic regions. Multivariate discriminant analysis confirmed the presence of region-specific centroids for different syllable constructs, but also showed a large overlap of their multiparametric boundaries across geographic regions. We propose that despite differences in the population-specific core construct of a syllable type, bats maximize acoustic variation across individuals within a population regardless of its overflow to neighboring populations.